ENHANCING TEACHERS’ FUNCTIONAL SKILLS THROUGH ENGLISH LANGUAGE AND CULTURAL EXPOSURE USING AI AND DIGITAL INFORMAL LEARNING IN SOUTHERN, PAKISTAN - Majeed, Muhammad Kashif; Ahmad, Tunku Badariah Binti (Journal of English Language and Culture, 2025)
In the digital age, educators must continuously adapt their functional skills to meet evolving classroom and communication demands. English language proficiency and cultural understanding are increasingly essential for teachers in multilingual and multicultural environments. Artificial Intelligence (AI) and digital informal learning have emerged as innovative tools to support this development, especially in underserved educational settings.Despite growing interest in AI in education, limited studies focus on how AI and informal digital platforms collectively contribute to English language acquisition, cultural awareness, and overall functional skills development among teachers, particularly in Islamic secondary schools in Southern Pakistan.The study is a quantitative experiment which examines how AI tools can help to improve the knowledge of English language, how digital informal learning leads to cultural awareness and how both can contribute to the development of functional skills wielded by teachers. The representative selection of 450 teachers in the Islamic secondary schools was chosen subserviently. An analysis of such data was undertaken by means of a structured questionnaire and SPSS (2021) using descriptive statistics and independent sample t-tests. The results demonstrate that AI-based tools are extremely helpful regarding the learning of the English language, and informal digital platforms increase the level of intercultural sensitivity in teachers. These are combined to have a positive contribution in the development of key functional skills like communication, critical thinking and problem solving. The research promotes changes to the education policy that should embrace AI and digital resources within the teacher development plans. It offers critical information to policymakers, educational leaders, and developers of EdTech who would wish to enable linguistically and culturally diverse areas teachers.